Determination of the spatial variability of soil nitrogen content based on reliefs in an apple orchard, Batu, Indonesia - Kurniawan Sigit Wicaksono; S Suratman; R Suharyadi; Sigit Heru Murti (Journal of Degraded and Mining Lands Management, 2019)
A better understanding of the spatial variability of soil nitrogen content is required to achieve the best management in precision agriculture. The purpose of this research was to determine the spatial variability of soil nitrogen content based on reliefs in an apple orchard. The research was conducted from March to August 2018 in a 1210 hectare of apple orchard, Batu, East Java Province, Indonesia. Soil samples were taken using the stratified random sampling method. Data were processed by the GLM Univariate 5% method with SPSS 16.0. The results of the statistical analysis show that the Sig value and coefficient of determination were 0.000 and 0.846, respectively. This condition means that soil nitrogen content was significantly different in various reliefs. The apple orchard was divided into 10 (ten) zones with different soil nitrogen content in various relief. It is crucial as a basis for implementing precision agriculture in apple orchards, meaning that the determination of fertilizer dosage is adjusted to the soil nitrogen content in the various zones. This study concluded that relief significantly affects the spatial variability of soil nitrogen content.